Gerakan Tarekat dan Pertumbuhan Budaya Berfilosofi di Lombok - Quddus, Abdul; Ariadi, Lalu Muhammad (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
In Indonesia, Sufism has become a focal part of the development of Islam from 13th to 18th century. Once Islam was widely spread out of Indonesia in 13th century, the teaching of Sufism had metamorphosed into a religious movement known as tarekat (Sufi order). Through tarekat movement, Islam in Indonesia has grew not only as a religion but also as a fundamental part of cultural entities in the country. Among these cultures is the Culture of Philosophy in Lombok. This article attempts to scrutinize the development of Tarekat Movement and the Culture of Philosophy in Lombok. These two aspects are analyzed through an anthropological study. The study finds that Tarekat Movement has played significant role in the growth of the Culture of Philosophy in Lombok. Through the Culture of Philosophy, the Muslim people in Lombok learn and understand Islam as a set of logical facts that teaches its adherents about the Divine Reality and wisdoms of life. This culture has been transmitted from generation to generation through oral and written transmissions, in which the written way is found within classical manuscripts. Through these media, the doctrines of Sufism have been taught as a means of cherishing the relation amongst God, Man, and Nature.